2005
DOI: 10.1038/sj.ijo.0802919
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and impaired glucose tolerance in obese children and adolescents referred to a tertiary-care center in Israel

Abstract: OBJECTIVE:To establish the prevalence of insulin resistance and impaired glucose tolerance (IGT) and their determinants in a cohort of obese children and adolescents. METHODS: A retrospective design was used. The study group included 234 patients with a body mass index (BMI) greater than the 95th percentile for age and gender and 22 patients with a BMI between the 85th and 95th percentile for age and gender referred for evaluation to a major tertiary-care center in Israel. Ages ranged from 5 to 22 y. Estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
47
4
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 56 publications
15
47
4
2
Order By: Relevance
“…19 Presence of AN can also be used as a grounds to initiate and reinforce discussions about lifestyle modification. 5,19,20 An observed AN frequency of 54% in our subjects was consistent with data reported in the Abbreviations: BMI = body mass index; HOMA-IR = homeostasis model of assessment-insulin resistance; SD = standard deviation * Acanthosis nigricans status was unavailable in 11 (2%) patients † HOMA-IR information was absent in 46 (8%) patients 21,22 Our adolescents were more likely to have AN than younger children, in line with hyperinsulinaemia being more severe among older individuals. 22 In our study, development of AN showed no gender preference, as in a study of 1412 unselected children by Stuart et al 23 In our cohort and that in Nsiah-Kumi et al's study, 13 obese children were more likely to have AN than overweight ones.…”
Section: Discussionsupporting
confidence: 79%
“…19 Presence of AN can also be used as a grounds to initiate and reinforce discussions about lifestyle modification. 5,19,20 An observed AN frequency of 54% in our subjects was consistent with data reported in the Abbreviations: BMI = body mass index; HOMA-IR = homeostasis model of assessment-insulin resistance; SD = standard deviation * Acanthosis nigricans status was unavailable in 11 (2%) patients † HOMA-IR information was absent in 46 (8%) patients 21,22 Our adolescents were more likely to have AN than younger children, in line with hyperinsulinaemia being more severe among older individuals. 22 In our study, development of AN showed no gender preference, as in a study of 1412 unselected children by Stuart et al 23 In our cohort and that in Nsiah-Kumi et al's study, 13 obese children were more likely to have AN than overweight ones.…”
Section: Discussionsupporting
confidence: 79%
“…The results showed a significant proportion of patients with obesity related comorbidities with hypertension being the most prevalent. However, there is a lower proportion of patients with dyslipidemia, impaired glucose tolerance and fatty liver in this study, compared to other studies [14,18,19], which is related to lower numbers of patients being screen for the metabolic complications. The expert committee's recommendations on childhood obesity suggest for fasting glucose, lipid panel.…”
Section: Discussioncontrasting
confidence: 40%
“…The prevalence of obesity in children and adolescents has reached epidemic proportions in both developed and developing countries (1). Insulin resistance in adults has been recognized for decades as a cardinal feature in the development of type 2 diabetes and has been associated with obesity, metabolic syndrome, hypertension, and heart disease (2, 3).…”
Section: Discussionmentioning
confidence: 99%